Kajian Arsitektur Masjid Teungku di Anjong, Banda Aceh: Rekonsiliasi Antara Tradisi dan Modernitas - Muhammad Ridho; Zya Dyena Meutia; Dedy Ruzwardy (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
The Peulanggahan Mosque in Banda Aceh serves as a historical landmark showcasing the architectural interplay between traditional Acehnese styles and modern construction techniques. This paper investigates the spatial evolution, functional transformation, and material adaptation of the mosque through qualitative analysis. Findings highlight the mosque’s pivotal role in preserving Islamic cultural heritage while adapting to contemporary needs. The research analyzes three primary aspects: (1) patterns of spatial expansion, (2) changes in functionality over time, and (3) reconciliation of traditional and modern architectural elements.